Implementation of speech pathology telepractice services for clinical swallowing assessment: An evaluation of service outcomes, costs and consumer satisfaction. (October 2019) - Burns, Clare L; Ward, Elizabeth C; Gray, Amy; Baker, Lisa; Cowie, Brooke; Winter, Natalie; Rusch, Rukmani; Saxon, Robyn; Barnes, Sarah; Turvey, Jodie
Introduction: Timely assessment of swallowing disorders (dysphagia) by speech pathologists helps minimise patient risk, optimise quality of life, and limit healthcare costs. This study involved a multi-site implementation of a validated model for conducting adult clinical swallowing assessments via telepractice and examined its service outcomes, costs and consumer satisfaction. Methods: Five hub-spoke telepractice services, encompassing 18 facilities were established across a public health service. Service implementation support, including training of the telepractice speech pathologists (T-SP) and healthcare support workers in each site, was facilitated by an experienced project officer. New referrals from spoke sites were managed by the hub T-SP as per published protocols for dysphagia assessments via telepractice. Data was collected on existing service models prior to implementation, and then patient demographics, referral information, session outcomes, costs and patient and T-SP satisfaction when using telepractice. Results: The first 50 sessions were analysed. Referrals were predominantly for inpatients at spoke sites. Telepractice assessments were completed successfully, with only minor technical issues. Changes to patient management (i.e. food/fluid changes post assessment) to optimise safety or progress oral intake, was required for 64% of patients. Service and cost efficiencies were achieved with an average 2-day reduction in waiting time and an average cost benefit of $218 per session when using the telepractice service over standard care. High clinician and patient satisfaction was reported. Conclusion: Telepractice services were successfully introduced across multiple sites, and achieved service and cost benefits with high consumer satisfaction.